PTH-035 Pulmonary Misplacement Of Nasogastric Tubes: A 2 Year Audit Of Service Delivery, Feedback Intervention And Patient Outcome. (9th June 2014) - Mansour, F; Virta, M; Neild, P; Marshall, T
Abstract : Introduction: Although nasogastric feeding will continue to be the preferred method of assisted nutrition, after oral intake, better understanding of the risks associated with pulmonary misplacement and how to improve delivery of service is required. It is well known that feeding through a pulmonary placed NGT can lead to serious harm or mortality. The National Patient Safety Agency (NPSA) issued guidelines in 2011 to try to reduce reported cases of feeding into the lungs. However, it is unknown whether the introduction of an NG tube into the lungs, in itself can introduce infection. Methods: We conducted two snapshot audits at a tertiary centre between 2012–2013. Between these audits, organised training of nursing and core medical trainees was conducted. Audits involved spot-checks on 34 wards, assessing notes of all patients with NGTs in situ that day. These were then compared to NPSA guidelines. We also did a retrospective study on the outcome of cases with pulmonary misplaced tubes, between 2012–2013. To identify these, chest X-ray reports were searched. Patient mortality and cases that later developed sepsis or chest infection were calculated. They were then compared to a group of controls that did have correctly placed NGTs. Results: The number of patients with NG tubes in situ were 38 and 46 in 2012 and 2013 respectively. None of these had cases of pulmonary misplacement. After the training that staff received there was a remarkable improvement in guideline adherence in 2013. Documentation of insertion increased by 46% (p < 0.001), and length of NGT recording increased by 53.9% (p < 0.001). pH checks being the first line confirmation of position, rather than X-ray, increased by 33.8% (p = 0.002). In the 18 patients that had pH checks in 2013, 7 patients did not require a second line Xray to check position. From the radiology search there were 27 patients that did have pulmonary misplacement out of a total of 1332 (2.03%). For mortality RR = 1.33 (95% CI: 0.8424 – 2.1077, P = 0.2199). For development of infection the RR = 1.94 which was statistically significant (95% CI: 1.1362 – 3.3207, P = 0.0152). Direct logistic regression was performed on patient age to assess the impact on the likelihood of developing disease. However, this was not found to be statistically significant. Conclusion: It appears that training of both nursing and medical staff can have a huge benefit in increasing adherence to guidance. This study suggests that patients are nearly twice as likely to develop chest infection or sepsis after pulmonary misplacement of their NGT. Although other factors such as age have been shown to have little affect on this outcome, factors such as patient morbidity before misplacement could not be assessed. Disclosure of Interest: None Declared.